Pengaruh Intellectual Capital Terhadap Kinerja Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Suprayogi, M. Dodik; Karjati, Pratiwi Dwi (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2020)
The Intellectual Capital concept emerged because of the industrial-based economic shift towards knowledge-based. From previous research it was known that IC had an effect on the company's financial performance. With the competitive advantage that the company has, it will improve the performance of the company itself. So that IC can be said as an intangible asset that has a significant impact on performance and all success in business. Therefore the author wants to examine more about